PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV C SDN 39 PEKANBARU - Fera Octha Nila Sari; Syahrilfuddin '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. This research is motivated by the low value of math. Preliminary data result of learning students of class IV C SD Negeri 39 Pekanbaru is from the 30 students, only 12 peoples or 40% completed or reached the KKM and 18 peoples or 60% were not completed. %. With the average value reached 67. Based on these problems, it is necessary given way to solve the problem include applying Contextual Teaching and Learning (CTL) model. Contextual Teaching and Learning (CTL) show the students the truth story and example from the real life of the lesson, then the students can understand the lesson well. This research is a classroom action research (PTK). Data collection instrument on this research are observation sheet activities of teacher and student, and learning outcomes. Subjects in this research were students of class IV C SD Negeri 39 Pekanbaru. This research was conducted in two cycles, by doing the daily test of the end of each cycle. This research was conducted in March of the school year 2014/2015 in the class IV C SD Negeri 39 Pekanbaru . This study presents an increase in the activity of teachers in the first cycle by good category anda rise 85.71% to 92.85% in the second cycle with excellent category, while the activities of students in the first cycle of 75% with the good category on the second cycle increased to 92.85% with very good category. Based on the research of student learning outcomes increased, visible from basic scored 67 increased to 76 in Daily test I at the end of the first cycle and increased again to 83 in Daily test II at the end of the second cycle. The result of this research shows that the Contextual Teaching and Learning (CTL) model can increase math studies, completeness math learning outcomes in first cycle is 66,6%, in second cycle increased to 83,3%.Keywords: Contextual Teaching and Learning (CTL), Mathematics Learning Outcomes.